Yazid,2024 Pengaruh Arus Lalu Lintas Kendaraan Di Ruas Jalan Arteri Kota Kediri Terhadap Pemetaan Emisi Gas Karbon Dioksida (CO2) Dan Suhu Permukaan Tanah - Fauzan, Yazid (Universitas Muhammadiyah Surabaya, 2024)
Kediri City is the oldest city in East Java and is located 130 km southwest of Surabaya City. This city is an enclave of Kediri Regency. Based on BPS data from the 2023 census, the population of Kediri City is 289,418 people. The numbers above will certainly affect the density of traffic flow in the city. Vehicle volume density also has an impact on the chemical substances released such as carbon dioxide (CO2), hydrocarbons (HC), lead (Pb), etc. Apart from that, vehicle volume also has an impact on increasing ground surface temperatures in road areas. In this research, the only things discussed are CO2 emissions and land surface temperature. The vehicle volume calculation uses the MKJI 1997 method, then mapping is carried out using ArcGIS. After conducting research, it was found that the highest vehicle volume was on segment I Jalan Diponegoro at 16.45-17.00 WIB at 5788.4 pcu/hour. The highest average CO2 emissions in segment II Jalan Basuki Rachmat are 745 ppm and the highest ground surface temperature is located during the afternoon peak hour in segment V Jalan HOS Cokroaminoto at 41.7°C.